Policies for Developing Vietnam's Science and Technology Human Resources: A Perspective from Reality - Thuy, Dao Thi Thuy (VNU Journal of Science: Policy and Management Studies; Vol 36 No 2DO - 10.25073/2588-1116/vnupam.4241, 2020)
Nowadays, the fourth industrial revolution and the extensive international integration process has posed many problems for S&T human resource development. The development of interdisciplinary and multi-disciplinary technology of the fourth industrial revolution not only brings opportunities but also poses great challenges to the requirements of building and developing S&T human resources. Machines and artificial intelligence replacing human power will inevitably result in the cheap, unskilled labor to be replaced by highly qualified human resources. Therefore, more than ever, the need to develop S&T human resources has become more urgent. In particular, the process of comprehensive international integration is imposing that S&T human resources must have update and global skills, keeping up with new trends in the development of S&T. Recently, the Government of Vietnam has determined the important role of S&T human resources and has issued a number of policies to develop S&T human resources, but these policies have not brought the expected results.